Hungarian Monitoring, 6 June 1988 . [Magyar rádiófigyelő], 1988. június 6 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - French election results - Soviet government's message to Orthodox church leaders - Large-scale Czechoslovak military practice - American presidential nominations Domestic Affairs: - Gorbachev's personal representative informs Károly Grósz about Moscow summit - President of the Republic of Finland a guest in Hungary - Mock's visit - Rajiv Gandhi before his weekend visit - Foreign Ministry's reaction to compulsory Romanian place name use - Situation of Roma Economy: - 70 million USD World Bank loan to Hungarian National Bank Külpolitika - Franciaországi választások eredménye - A szovjet kormány üzenete az ortodox egyház vezetőinek - Nagyszabású csehszlovák hadgyakorlat - Amerikai elnökjelölő választások Belpolitika - Grósz Károlyt Gorbacsov személyes képviselője tájékoztatta a moszkvai csúcsról - Hazánk vendége a Finn köztársasági elnök - Mock látogatás - Radzsiv Gandhi hétvégi látogatása előtt - A külügyminisztérium reakciója a kötelező román helységnévhasználat - A cigányság helyzete Gazdaság: - 70 millió dolláros világbanki hitel az MNB-nek